Lumboperitoneal shunt for the treatment of leptomeningeal metastasis. Issue 5 (May 2015) - Zhang, Xiao-Hui; Wang, Xiao-Guang; Piao, Ying-Zhe; Wang, Peng; Li, Peng; Li, Wen-Liang
Abstract Leptomeningeal metastasis (LM) is thought to be a devastating and increasingly frequent neurological complication of cancer characterized by infiltration of malignant cells into the leptomeninges and the subarachnoid space. Intracranial hypertension and hydrocephalus are observed in about half of patients with LM. They are responsible for rapidly declining neurological status and eventual poor outcome in many patients with LM. Impediment of CSF circulation is considered the pathophysiological basis of increased intracranial pressure and hydrocephalus related to LM, which makes ventriculoperitoneal shunt (VP shunt) an acceptable palliative approach for LM now. It is noteworthy that LM generally causes communicating hydrocephalus. Lumboperitoneal shunt (LP shunt) has been demonstrated to be effective in the treatment of communicating hydrocephalus secondary to hemorrhage or infection, idiopathic intracranial hypertension and normal pressure hydrocephalus. And LP shunt has several advantages over VP shunt. Therefore we hypothesize that LP shunt can be used in the treatment of intracranial hypertension and hydrocephalus related to LM and should be given greater priority over VP shunt.